2020
DOI: 10.1177/1473325020940774
|View full text |Cite
|
Sign up to set email alerts
|

“I’m meant to be his comfort blanket, not a punching bag” – Ethnomimesis as an exploration of maternal child to parent violence in pre-adolescents

Abstract: This is the first study to use ethno-mimesis to explore the lived experiences of mothers navigating child-to-parent violence initiated by pre-adolescent children. The current child-to-parent violence research landscape is predominantly focused upon the experiences of parents of adolescent children, identifying that violent behaviours can be used as a life-long strategy. This research uses innovative methods to explore the lived experiences of mothers, and how they understand and navigate the violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Intrusive behaviors may also lead to anxiety by limiting the young person's perceptions of control (Nanda et al, 2012). Recent qualitative work by Rutter (2021) aligns with this conceptualization, describing a process surrounding an overwhelmed young person whose violence is unintended, nondirected, and anxiety based.…”
Section: Discussionmentioning
confidence: 99%
“…Intrusive behaviors may also lead to anxiety by limiting the young person's perceptions of control (Nanda et al, 2012). Recent qualitative work by Rutter (2021) aligns with this conceptualization, describing a process surrounding an overwhelmed young person whose violence is unintended, nondirected, and anxiety based.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in relation to anxiety and depression symptoms, a classic study found that parents involved in CPV had higher levels of both symptoms solely because they were conscious of the situation in which they were involved [62]. In addition, parents may struggle with daily life issues, along with feelings of self-blame, impotence, and insecurity [26,28,63], which are stressors that increase their vulnerability to anxiety and depression [64]. Moreover, in terms of obsessive-compulsive symptoms, parents tend to feel the need to be hypervigilant and keep their guard up at all times in their family environment [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a recent scoping review, parents described feelings of self-blaming, impotence, insecurity, social isolation, and a lack of support [27]. Thus, the available research suggests that CPV may have a negative impact on the mental health of parents [28].…”
Section: Cpv and Psychological Symptoms In Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further coding by Emma to sort data, with themes and sub-themes ordered hierarchically (Rutter, 2020).…”
Section: Our Research Processesmentioning
confidence: 99%